TAMI-56. TARGETING AMINO ACID METABOLIC VULNERABILITIES IN IDH-MUTANT AND IDH-WILDTYPE GLIOMAS. (12th November 2021) - Ohba, Shigeo; Hirayama, Akiyoshi; Hitachi, Keisuke; Yamaguchi, Hisateru; Mukherjee, Joydeep; Pieper, Russell; Hirose, Yuichi
Abstract: IDH-wildtype glioma and IDH-mutant glioma have different genetical and metabolic background although their histological appearances are similar. The aim of the study is to reveal the difference in metabolites between IDH-wildtype glioma and IDH-mutant glioma, and to find the effective treatment targeting cancer metabolism according to the status of IDH in gliomas. Two artificial cell lines made from normal human astrocyte were used: NHAE6E7hTERTRas (IDH-wildtype) and NHAE6E7hTERTIDHmut (IDH-mutant). Capillary electrophoresis time-of-flight-mass spectrometry (CE-TOFMS) revealed that the amount of asparagine was lower in NHAE6E7hTERTRas cells compared with NHAE6E7hTERTIDHmut cells. L-asparaginase, which converts asparagine into aspartate, was more effective in the former cells than the latter cells. L-asparaginase induced autophagy and inhibition of autophagy by 3-MA suppressed L-asparaginase-induced antitumor effect. Adding asparagine into the culture medium rescued the antitumor effect of L-asparaginase. L-asparaginase increased the expression of asparagine synthetase (ASNS) and genetical or pharmacological inhibition of ASNS enhanced the antitumor effect of L-asparaginase. CE-TOFMS showed the lower amount of glutamine, glutamate and 2-oxoglutarate in NHAE6E7hTERTIDHmut cells than NHAE6E7hTERTRas cells. GLUD1 inhibitor inhibited proliferation by inducing higher ROS level and apoptosis in NHAE6E7hTERTIDHmut cells than NHAE6E7hTERTRas cells. ROS inhibitor, NAC suppressed GLUD1 inhibitor-induced ROS, apoptosis, and cytotoxicity in NHAE6E7hTERTIDHmut cells. Exogeneous dimethyl 2-oxoglutarate rescued the cytotoxicity induced by GLUD1 inhibitor. L-asparaginase and GLUD1 inhibitor will be new therapeutic option for IDH-wildtype glioma and IDH-mutant glioma, respectively.